2014
DOI: 10.1136/bjsports-2014-093745
|View full text |Cite
|
Sign up to set email alerts
|

More than 50% of players sustained a time-loss injury (>1 day of lost training or playing time) during the 2012 Super Rugby Union Tournament: a prospective cohort study of 17 340 player-hours

Abstract: Abstract:Background: Professional rugby union is a contact sport with a high risk of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 10 publications
10
59
3
1
Order By: Relevance
“…The proportion of injured players (injured player proportion, IPP) (also known as a period prevalence) was calculated as the per cent of players injured during the tournament. In addition, the IPP for different grades of injury severity was also reported 5. The burden of match injuries in the 5-year period was calculated as days lost per 1000 match hours.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of injured players (injured player proportion, IPP) (also known as a period prevalence) was calculated as the per cent of players injured during the tournament. In addition, the IPP for different grades of injury severity was also reported 5. The burden of match injuries in the 5-year period was calculated as days lost per 1000 match hours.…”
Section: Discussionmentioning
confidence: 99%
“…However, no link has yet been established for injuries. Fuller et al 217 and Schwellnus et al 218 found no evidence to suggest that extensive air travel and crossing multiple time zones led to an increase risk of injury in elite rugby union players. Similarly, Fowler et al 219 observed no significant effect of regular national travel on recovery or injury rate in professional Australian soccer players.…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 98%
“…Lower extremity injuries are prevalent across the football codes including soccer,1 Australian rules football,2 gaelic football,3 rugby league,4 rugby union5 and American football 6. Elite soccer players sustain an average of two injuries per season1 and collegiate American football players have approximately five injuries per 1000 h of playing/practice exposure to their lower limbs 6.…”
Section: Introductionmentioning
confidence: 99%